Bilateral High-Origin Anterior Tibial Arteries and Its Clinical Importance - Sharma, K; Haque, MK; Mansur, DI (Kathmandu University Medical Journal, 2012)
Reported here is a case of bilateral high - origin anterior tibial arteries as detected during routine dissection of a 40 years old male cadaver at the Kathmandu University School of Medical Sciences, Kavre District, Nepal. The aim of the present study was to underline the clinical importance of high origin of anterior tibial artery from the popliteal artery.The high origin anterior tibial artery from the popliteal artery and its relations with the popliteus muscle is an important anatomical variation which should be paid attention during knee joint surgery, total knee arthroplasty and angiographic evaluations. KATHMANDU UNIVERSITY MEDICAL JOURNAL VOL.10 | NO. 1 | ISSUE 37 | JAN - MAR 2012 | 88-90 DOI: http://dx.doi.org/10.3126/kumj.v10i1.6923